2003
DOI: 10.1063/1.1619362
|View full text |Cite
|
Sign up to set email alerts
|

Activation spectroscopy of electronically induced defects in solid Ne

Abstract: Thermally stimulated luminescence (TSL) and thermally stimulated exoelectron emission (TSEE) methods were used in combination with cathodoluminescence to probe electronically induced defects in solid Ne. The defects were generated by a low energy electron beam. For spectroscopic study we used Ar * centers in Ne matrix as a model system. At a temperature of 10.5 K a sharp decrease in the intensity of «defect» components in the luminescence spectrum was observed. From the analysis of the corresponding peak in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 14 publications
3
19
1
Order By: Relevance
“…A pronounced maximum, which is interpreted as being due to the annealing of the exciton-induced defects was observed in the range 10-11 K in both TSL and TSEE yields of solid Ne. The activation energies E d experimentally found [16,17] for this type of electron traps (E d =28, 18 and 20 meV obtained by isothermal decay, different heating rates, and halfwidth methods) are in good agreement with the theoretical results [6]. In solid Ar, exciton-induced defects are annealed at about 15 K as was found in Refs.…”
Section: Resultssupporting
confidence: 81%
“…A pronounced maximum, which is interpreted as being due to the annealing of the exciton-induced defects was observed in the range 10-11 K in both TSL and TSEE yields of solid Ne. The activation energies E d experimentally found [16,17] for this type of electron traps (E d =28, 18 and 20 meV obtained by isothermal decay, different heating rates, and halfwidth methods) are in good agreement with the theoretical results [6]. In solid Ar, exciton-induced defects are annealed at about 15 K as was found in Refs.…”
Section: Resultssupporting
confidence: 81%
“…Therefore, thermo-or photostimulated electrons leave the traps and initiate neutralization reactions. It was shown that such electrons are responsible for luminescence observed in cryocrystals [39,41]. We suggest similar processes were observed in cryocondensates [42][43][44] and impurity nanoclusters [23] at temperatures below 10 K when the atoms are still immobile in solids.…”
Section: "Cold" and "Hot" Thermoluminescence Spectra From Ihcssupporting
confidence: 68%
“…Some impurity centers as well as different structural defects of cryocrystals and clusters can be such electron traps. There are very broad distributions of electron traps in cryocrystals and clusters on the activation energy: the activation energies of 3.5 and 20 meV were determined for structure defects in neon nanoclusters [23] and cryocrystals [39], respectively, while the electron affinity energy of O( 3 P) atom is of 1.46 eV [40]. Therefore, thermo-or photostimulated electrons leave the traps and initiate neutralization reactions.…”
Section: "Cold" and "Hot" Thermoluminescence Spectra From Ihcsmentioning
confidence: 99%
“…For this purpose we developed a low temperature modification of correlation spectroscopy, i.e., simultaneous measurements of TSL, TSEE and desorption of neutral atoms [8] from pre-irradiated RGS. In our previous experiments, TSEE was detected from solid Ar [9] and Ne [10,11]. In this article we present our results of an activation spectroscopy study in solid Xe pre-irradiated with an electron beam.…”
Section: Introductionmentioning
confidence: 81%